Access to primary healthcare services by people with disabilities - Paula Marciana Pinheiro de Oliveira; Gisele Mendes da Silva; Neucilia Oliveira Silva; Sonha Maria Coelho de Aquino; Dandara Araújo Viana; Edmara Chaves Costa; Andressa Suelly Saturnino de Oliveira (Universidade Federal do Ceará, 2023)
Objective: to analyze the access of people with hearing, physical, and visual disabilities to primary healthcare services. Methods: a cross-sectional study was conducted with 250 participants, and data collection was implemented in three stages: contact with the health department, locating the residences of persons with disabilities within the coverage area of the primary healthcare unit, and analysis of integrated data. Results: there was a predominance of older individuals, individuals of non-white race/ethnicity, males, and those who were either married or in a consensual union. Self-transportation, including cars, motorcycles, or bicycles, was the primary means of access to services, followed by walking. Most individuals sought health services within six months, followed by those who sought care between six months and one year, mainly because of chronic or worsening conditions. Conclusions: impaired access was identified, as evidenced by multiple barriers, including transportation, architectural, and communication barriers. Contributions to practice: it is important to consider the disparities, vulnerabilities, and health status of the disabled population in health care.